KHAYOM LAKPA: THE CASE OF PHAYENG (International Journal of Food and Nutritional Sciences, 2023)
Khayom lakpa is one of the traditional healing practices of the warding of seriously ill person by a maiba or maibee (a man or a woman who performs rituals as a priest, and as a medicine man, who can cure and act as shaman who performs magic that may be black/white and performs a ritual for the benefit of a person, a family or a community) by giving a khayom. Khayom is made of three banana leaves, an egg of duck, three buds of langthrei (Eupatorium odoratum), a piece of gold and apiece of silver (they are replaced by a red and white rice) inside it. This can be done in three ways viz, leithak lakpa, leikha lakpa and leithak leikha lakpa. The nature of making khayom is in different ways in three kinds of khayom lakapa. Other requirements for the ritual are heiram taret (seven varieties of fruit), leiram taret (seven varieties of flower), kabok nachal taret (seven handful of roasted rice), huibi mana (leaves of vangueria spinosa plant) salt, chili, pukyu (a kind of local wine), cheng (rice) sana konyai ( a piece of gold), lupa konyai (a piece of silver). For the purpose of Irai Leima an other egg of hand is required. In some cases yelhing thaba is associated with khyom lakpa. Yelhing is offering of a yenbaraba (a mature cock) to the god of the four corner. For God Thajing the colour of the cock is Red, for the God Wangbren mixed of some colour, for God Marjing the colour of the cock is white and black is for the God Koubhru. In the community level, khayom lakpa is performed in the first day of Lai-haraoba festival of Meiteis.